A Bibliometric Review of Renewable Energy Financing and Sustainable Development - Judijanto, Loso; Nampira, Ardi Azhar; Auliani, Restu; Sinaga, Jernita (West Science Social and Humanities Studies, 2025)
This study presents a comprehensive bibliometric review of the scholarly literature on renewable energy financing and its link to sustainable development. Utilizing data from the Scopus database and analyzed through VOSviewer, the study maps thematic clusters, keyword co-occurrences, author collaborations, and country-level partnerships from 2000 to 2024. The findings reveal that "sustainable development" serves as the conceptual core of this research domain, closely associated with terms such as "green finance," "energy efficiency," and "climate change." Recent trends indicate a growing scholarly focus on financial instruments like green bonds and the broader policy landscape of energy transition. Co-authorship and country collaboration networks demonstrate strong regional concentrations, with China, the United States, and India emerging as key contributors. While the literature is rich in financial and technological insights, gaps remain in addressing social equity, regional financing models, and the integration of digital finance. This study contributes to the literature by offering a systematic overview of research developments, identifying influential contributors, and suggesting future directions for interdisciplinary inquiry into sustainable energy finance.